Salmonella enterica and outer membrane vesicles are current and future options for cancer treatment - Pérez Jorge, Genesy; Gontijo, Marco Túlio Pardini; Brocchi, Marcelo (Frontiers in Cellular and Infection Microbiology, 2023)
Conventional cancer therapies have many limitations. In the last decade, it has been suggested that bacteria-mediated immunotherapy may circumvent the restrictions of traditional treatments. For example, Salmonella enterica is the most promising bacteria for treating cancer due to its intrinsic abilities, such as killing tumor cells, targeting, penetrating, and proliferating into the tumor. S. enterica has been genetically modified to ensure safety and increase its intrinsic antitumor efficacy. This bacterium has been used as a vector for delivering anticancer agents and as a combination therapy with chemotherapy, radiotherapy, or photothermic. Recent studies have reported the antitumor efficacy of outer membrane vesicles (OMVs) derived from S. enterica. OMVs are considered safer than attenuated bacteria and can stimulate the immune system as they comprise most of the immunogens found on the surface of their parent bacteria. Furthermore, OMVs can also be used as nanocarriers for antitumor agents. This review describes the advances in S. enterica as immunotherapy against cancer and the mechanisms by which Salmonella fights cancer. We also highlight the use of OMVs as immunotherapy and nanocarriers of anticancer agents. OMVs derived from S. enterica are innovative and promising strategies requiring further investigation.